World's first large size 77‐inch transparent flexible OLED display - Park, Chan Il; Seong, Miryn; Kim, Mi Ae; Kim, Dojin; Jung, Hyunju; Cho, Mingu; Lee, Sang Hoon; Lee, Hyokang; Min, Sungjoon; Kim, Jaehyeong; Kim, Minseok; Park, Jong‐Hyun; et al. (Journal of the Society for Information Display, 2018)
Large flexible organic light‐emitting diode (OLED) display provides various electronic applications such as curved, bendable, rollable, and commercial display, because of its thinness, light weight, and design freedom. In this work, the process flow and key technologies to fabricate the world's first large size 77‐inch transparent flexible OLED display are introduced. “White OLED on TFT + color filter” method is used to fabricate the aforementioned display. On both thin‐film transistor and color filter substrates, transparent polyimide (PI) was used as plastic substrate with multi‐barrier. In case of a transparent flexible display, the multi‐barrier is required for the additional consideration to overcome the decrease of transmittance due to the difference in refractive index of the conventional multi‐barrier. We developed the special multi‐barrier to increase transparency with superior water vapor transition rate characteristic. The optimized amorphous indium gallium zinc oxide thin‐film transistors were employed on the multi‐barrier, and it shows the highly uniform electrical performance and reliability on plastic substrate. Also, the typical panel failure mechanism during laser lift‐off process caused by a particle in PI is studied, and a sacrificial layer was suggested between PI and a carrier glass to reduce the panel failure. Finally, we successfully realized the world's first 77‐inch transparent flexible OLED display with ultra‐high‐definition resolution, which can be rolled up to a radius of 80 mm with a transmittance of 40%. We successfully realized the world's first large size 77‐inch transparent flexible display with ultra‐high‐definition resolution, which can be rolled up to a radius of 80 mm with a transmittance of 40%. The process flow and key technologies to fabricate a large size transparent flexible organic light‐emitting diode panel is introduced.